A synthesised view of process improvement methodologies within the English NHS: A systematic review of empirical case studies - Kerrigan, Matthew David (2022)
Background: The COVID-19 pandemic has acted as a catalyst globally for healthcare organisations to rethink and evaluate their processes due to the strain of the pandemic (Kuiper et al., 2021; Ortíz-Barrios & Alfaro-Saíz, 2020; Silver et al., 2021; Hill et al., 2021). This has presented a unique opportunity to explore the emerging themes within this industry. One of the key themes of the NHS Long Term plan is the overall improvement of NHS processes. These improvements must be completed at trust level, and so the sharing of best practice and lessons learned will be fundamental to the achievement of these goals, which is itself a key issue within the NHS (Matthias & Brown, 2016). Due to this approach, there is likely to be variation, as healthcare practitioners, similar to other industries, prefer to use a set of techniques usually due to personal preference or local context (Rizan et al., 2020). Objectives: The objective of this paper is to provide a synthesised, holistic view of process improvement methodologies within the English NHS. This research reviewed the existing literature that concerned process improvement programmes within the NHS to examine and extract key, emerging themes, and commonalities to aid in the creation of the synthesised view which intends to inform the literature and those with a vested interest in the NHS. Methods: A systematic literature review of NHS England case studies was conducted. A search strategy was applied to Web of Science, PubMed and Scopus to extract relevant references. A total of 4831 unique results were returned and subsequently reviewed. Following the first full text review, additional criteria were added to refine the scope of the study. Data were then extracted into a meta- framework, where variables were geared towards the research questions. Results: A total of 95 studies were found to be eligible following the application of exclusionary criteria. The most used methodologies were PDSA, Model for Improvement and Lean. A range of process improvement tools were also identified. Positive and negative influences on sustainability were identified, with influences such as junior doctor rotations and cost effectiveness being some examples. There were three methods used to report sustainability: quantitative proof of sustainment, qualitative confirmation that elements are still embedded, and use of sustainability model.